Knowledge, attitude and practices about adverse drug reaction among medical students in a medical college: an observational study - ., Roshi; Tandon, Vishal R.; Gupta, Brij M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse Drug Reactions (ADRs) are usually associated with drugs which may or may not go unnoticed. ADRs are of great concern for any health care set up as they directly or indirectly add to the cost of treatment, prolongation of treatment, hospital stay or sometimes may even cause death. Spontaneous ADR reporting forms an important part of pharmacovigilance. Methods: An observational study was carried out in a medical college to know the knowledge, attitude and practice being followed by them in a Medical College. Results: In present study all the students had knowledge about ADRs. Only 86.7% of the students knew how and where to report an ADR. 73.3% of the students knew who can report an ADR and they had visited ADRM centre but only 60% of the students knew which ADR is to be reported. 88% of the students had an attitude that it is important to report an ADR and 86.7% told that it is useful to report an ADR. 99.3% of the students had never reported an ADR. Only 1.4% of the students had really visited ADRM centre of their institution but none of the students had ever visited wards or OPDs to look for ADRs. 26.7% of the students said that they will report an ADR if they see it ever. Conclusions: There is good knowledge about ADRs and ADRM centre among students, but it needs to bring ADR reporting into practice by actively doing hands on workshops or by adding this exercise into practical curriculum.